2020
DOI: 10.1002/pchj.340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transfer type on labor's role in ownership judgments

Abstract: Many property issues in real life occur in the transfer contexts. Previous studies have investigated the role of creation and value change in people's use of the labor rule when solving property issues involving conflicting cues between labor and first possession, but have neglected the possible effect of transfer types. This study explored how items get transferred from the original owner to the next affected adults' use of the labor rule when assigning ownership. Eighty‐two participants (Mage = 22.10 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…They found that children above 10 years old and adults would not support the modifier as the owner of the falcon, even if the value of the wood had appreciated greatly. The same result was also found in Chinese adult samples ( Li et al, 2019 ).…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…They found that children above 10 years old and adults would not support the modifier as the owner of the falcon, even if the value of the wood had appreciated greatly. The same result was also found in Chinese adult samples ( Li et al, 2019 ).…”
Section: Introductionsupporting
confidence: 83%
“…They found that children above 10 years old and adults would not support the modifier as the owner of the falcon, even if the value of the wood had appreciated greatly. The same result was also found in Chinese adult samples (Li et al, 2019). Recently, Li et al (2020) examined Chinese adults' ownership assignments when faced with disputes between the original owner and the modifier in three transfer contexts (i.e., keep, borrow and find).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…It’s commonly acknowledged that the legitimacy of an obtaining object will affect ownership assignments between the original owner and the obtainer. A recent study [ 35 ] examined how Chinese adults assign ownership when someone’s objects are acquired and modified by another person in different ways (kept, borrowed, found). It was found that adults believed that the modified objects still belong to the original owner when they were just kept by the modifier, but they belong to the modifier when they were lost by the original owner and found by the modifier.…”
Section: Limitation and Future Studiesmentioning
confidence: 99%